Profile of inborn errors of metabolism among the neonates admitted in special newborn care unit of a tertiary care hospital - Kushal Mandal; Sushama Sahoo; Sarbani Misra; Bharat Lal Kisku (Asian Journal of Medical Sciences, 2025)
Background: Inborn errors of metabolism (IEM) refer to a group of hereditary disorders that occur due to the disruption of normal biochemical processes in the body. Although the incidence of IEM is rare, together their incidence is more than 1:1000.1 IEM usually presents with non-specific symptoms, which could only be ruled out by the presence of a high level of suspicion of the disease. This study shares our experiences of different presentations and incidences of metabolic disorders by doing tandem mass spectrometry and highlights the importance of metabolic screening as a part of routine newborn screening.